Hematology and clinical biochemistry reference intervals for companion pigs using the ADVIA 2120 and Cobas c501 - Deanna M. W. Schaefer; Ricardo Videla; Joe S. Smith; Pierre-Yves Mulon; Bente Flatland; Xiaojuan Zhu (PeerJ)
Background The majority of published reference intervals for hematology and clinical biochemistry in pigs are generated from a sample group that is demographically different from companion pigs, and as such may not be transferable. The goals of this study were to provide reference intervals generated from sexually mature companion pigs and to compare results based on age group, breed, and reproductive status. Reference intervals are ideally generated in the same laboratory in which patient samples are measured, since there is often bias in values generated from different instruments, but the cost and time commitment required to produce reference intervals may be prohibitive. If so, published reference intervals may be used cautiously as guidelines for interpretation. Methods Complete blood count (CBC) and plasma biochemistry data were generated using the ADVIA 2120 hematology analyzer and Cobas c501 chemistry analyzer on blood samples collected from 94 sexually mature, clinically healthy companion pigs housed mostly in eastern Tennessee over a 5-year period. The majority (90/94) of samples were collected after sedation or general anesthesia. The age range of the reference sample group was 5 months to 11 years, including <1-year-old (n = 26), 1–2 years old (n = 26), and >2-years-old (n = 42). Reproductive status included intact females (n = 46), spayed females (n = 9), intact males (n = 15), and castrated males (n = 24). Breeds were predominantly Vietnamese potbellied mini pigs, American mini pigs, and mixed breed pigs. Results Reference intervals are provided for routine CBC and plasma biochemistry values. The <1-year-old pigs were excluded from reference interval calculation for some values because their results were significantly different from pigs >1-year-old. These included red blood cell concentration, mean cell volume, mean cell hemoglobin, platelet count, mean platelet volume, lymphocyte concentrations by both automated and manual methods, and total protein by refractometry. Few significant differences were observed based on breed or reproductive status. Discussion Age, breed, and reproductive status can affect some hematology and biochemistry results in companion pigs. If companion pig reference intervals are not available from the laboratory in which patient samples are measured, these published reference intervals may provide guidance for interpretation, although some methodologic variances are likely.